1974
DOI: 10.1002/ar.1091780403
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mineralization of the tibial epiphyseal plate in the rat following propylthiouracil treatment: A histochemical, light, and electron microscopic study

Abstract: Following treatment with propylthiouracil, most chondrocytes in the reserve and upper proliferation zones in the tibial epiphyseal plate exhibit degenerate ultrastructural morphology. In the extracellular matrix, sulfated mucopolysaccharide is reduced, matrix vesicles are increased both in number a n d i n size, apatite crystals are present in all zones, and mineralization is enhanced.In post-treatment recovery, chondrocyte degeneration decreases; however, the extracellular matrix is considerably delayed in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…6, 10). DEARDEN [19] reported such findings in the cells of the resting and proliferating zone of epiphysial cartilage in the tibia of rats suffering characteristic regressive changes due to 6propylthiouracil administration for growth inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…6, 10). DEARDEN [19] reported such findings in the cells of the resting and proliferating zone of epiphysial cartilage in the tibia of rats suffering characteristic regressive changes due to 6propylthiouracil administration for growth inhibition.…”
Section: Discussionmentioning
confidence: 87%
“…According to Wuthier et al (1977), matrix vesicles are formed by a rapid, metabolically active process, not by degenerative changes in the cell membrane. On the other hand, the frequent report that matrix vesicles are located around degenerating chondrocytes (Hayashi et al 1993) or can be found collected in groups reminiscent of chondrocyte lacunae suggests that they may also derive from the degeneration and fragmentation of chondrocytes (Bonucci 1970a(Bonucci , 1978Dearden 1974;Bonucci and Dearden 1976;Akisaka and Shigenaga 1983;Akisaka and Gay 1985a;Reinholt et al 1982Reinholt et al , 1984. This process has long been known as "Verdämmern der Zellen" ('vanishing of cells'; Schaffer 1930) and is now thought to be a possible expression of cellular apoptosis (Kim 1976;Kardos and Hubbard 1982;Anderson 1995;Hashimoto et al 1998;Lotz et al 1999), a process that has been induced experimentally in articular cartilage (Hashimoto et al 1998) and that seems to characterize the terminal phase of hypertrophic chondrocytes (Rauterberg and Becker 1970;Kim 1995;Zenmyo et al 1996;Gibson et al 1997;Szuwart et al 1998;Magne et al 2003).…”
Section: Matrix Vesiclesmentioning
confidence: 99%